Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.apenergy.2016.10.105
|View full text |Cite
|
Sign up to set email alerts
|

Considering economic and geological uncertainty in the simulation of realistic investment decisions for CO2-EOR projects in the North Sea

Abstract: h i g h l i g h t sPSS IV, a techno-economic model for simulating CO 2 -EOR projects, is presented. Investment risk and uncertainty play a central role in our methodology. A North Sea case study for the Claymore and Scott field is developed. Case study results show a 30% value increase for the cluster approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…High risk is one of the most distinguishing features of international oil and gas (OG) projects. Suslick and Schiozer (2004) and Welkenhuysen et al (2017) suggested that geological risk, economic risk and engineering risk should all be considered because they influence the exploration and development of OG projects. As both geological risk and engineering risk affect the uncertainty of volumes and production plans of oil and gas projects, we propose to use resource risks to represent geological risk and engineering risk.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…High risk is one of the most distinguishing features of international oil and gas (OG) projects. Suslick and Schiozer (2004) and Welkenhuysen et al (2017) suggested that geological risk, economic risk and engineering risk should all be considered because they influence the exploration and development of OG projects. As both geological risk and engineering risk affect the uncertainty of volumes and production plans of oil and gas projects, we propose to use resource risks to represent geological risk and engineering risk.…”
Section: Introductionmentioning
confidence: 99%
“…However, the probability of different scenarios cannot be obtained. (4) The minimum expected return rate method, which aims to estimate the minimum expected return rate of a project under given parameters (Weijermars et al 2017;Welkenhuysen et al 2017). Although this method can be used to estimate the benchmark, the corresponding confidence level cannot be obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The usefulness of geostatistics in fisheries has been well established (Morfin et al, 2012;Petitgas et al, 2014;Rufino, Gaspar, Maynou, & Monteiro, 2008;Rufino, Maynou, Abelló, Gil de Sola, & Yule, 2005;Rufino, Maynou, Abelló, Yule, & Gil de Sola, 2006;Saraux et al, 2014). Space-time geostatistics have been used in other research fields, such as high-resolution global temperature (Kilibarda et al, 2014), precipitation (Raja, Aydin, Türkoğlu, & Çiçek, 2017), economy (Welkenhuysen et al, 2017), disease mapping (Marek, Tuček, & Pászto, 2015), reconstruction of past conditions using tree ring data (Biondi, 2013), and parasite propagation (Hu et al, 2015), but to the authors' best knowledge, these methods have never been applied in the field of fisheries biology. On the other hand, the patterns of temporal series of continuous maps can be summarized using empirical orthogonal functions analysis, a method similar to a principal component analysis (PCA), and often used in meteorology, but in the spatio-temporal domain (Morfin et al, 2012;Petitgas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The study also concluded that depleted gas reservoirs with low abandonment pressures and weak aquifer invasion, such as some reservoirs in the North Sea, are appealing for CO 2 sequestration as the CO 2 storage capacity could potentially equal the extracted gas volume. Many publications on CO 2 sequestration in depleted gas reservoirs have addressed different aspects, such as the CO 2 flow and trapping mechanisms, storage capacity, reservoir containment, risk assessment, and geomechanics [20][21][22][23][24][25][26].In this work, we investigate a serious flow-assurance issue that arises during CO 2 injection into depleted gas reservoirs when the abandonment reservoir pressure is below the CO 2 bubble-point pressure. This work is inspired by a potential CO 2 sequestration project in a depleted gas reservoir in the North Sea [27,28].…”
mentioning
confidence: 99%